Augmentation of antitumor function of tumor‐infiltrating lymphocytes against triple‐negative breast cancer by PD‐1 blockade. (9th December 2021) - Song, Hongming; Wang, Haibo; Gong, Mingkai; Wu, Li; Liu, Xiangping; Cao, Weihong; Gao, Xueqiang; Dou, Rongrong; Chen, Qiaoyu; Hu, Haiyan
Abstract: T‐cell‐based immunotherapy and immune checkpoint blockade have been successfully used to treat several human solid cancers. The present study attempted to investigate the feasibility and efficacy of the antitumor effect of adoptive cell therapy along with programmed cell death protein 1 (PD‐1) inhibitor on triple‐negative breast cancer (TNBC). Tumor infiltration lymphocytes (TILs) from TNBC mouse tumor tissues were isolated and expanded, and TILs for adoptive cell therapy (TILs‐ACT) were applied in combination with a PD‐1 inhibitor to the TNBC mouse model. The pre‐ and post‐therapy antitumor efficacy, cytokine secretion, and pathological changes were assessed both in vitro and in vivo. We found that TILs exhibited higher IFN‐γ and TNF‐α secretion than conventional T cells. The TILs‐ACT combined with PD‐1 inhibitor promoted active T‐cell infiltration into the tumor tissue and exerted a strong antitumor effect in an in vivo model. Additionally, the strategy could downregulate the expression of inhibitory marker PD‐1 on TILs. In conclusion, PD‐1 blockade regulated T‐cell exhaustion that synergized with adoptive TIL transfer immunotherapy, leading to eradication of established TNBC tumors. These findings might be useful in developing a feasible and effective therapeutic approach for TNBC.